2012
DOI: 10.1016/j.apsoil.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of earthworm communities and species traits in relation to the perturbation gradient of a restored floodplain

Abstract: a b s t r a c tLittle is known about the diversity and ecology of earthworms in floodplains, as well as their response to natural and anthropic perturbations (e.g. floods, river channelisation, floodplain restoration). We characterised the patterns of earthworm communities and species traits in the different habitats of a lowland restored floodplain in Switzerland. In addition to classical species-based metrics, such as species richness and Shannon diversity, species traits were used to calculate the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
(62 reference statements)
3
27
0
Order By: Relevance
“…Such increased burrowing activity could be due to a facilitative effect of intense rainfall (i.e., conditions were favourable for digging), or on the contrary it could indicate that the earthworms were stressed by the disturbance and tried to escape or improve their habitat conditions. Regarding L. terrestris survival and growth, it has been shown that high soil moisture may be favourable (Berry and Jordan 2001), while prolonged flooding is detrimental (Fournier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such increased burrowing activity could be due to a facilitative effect of intense rainfall (i.e., conditions were favourable for digging), or on the contrary it could indicate that the earthworms were stressed by the disturbance and tried to escape or improve their habitat conditions. Regarding L. terrestris survival and growth, it has been shown that high soil moisture may be favourable (Berry and Jordan 2001), while prolonged flooding is detrimental (Fournier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…High N0 indicates a large number of species and high N2 a large number of species evenly distributed. Strong relations between N0 and N2 and environmental conditions were demonstrated at various spatial scales [34] and in a broad range of ecosystems such as tropical forest [35], marine ecosystems [36] and flood or fire prone ecosystems [28,37,38]. N0 and N2 were calculated for each treatments and time step.…”
Section: Numerical Analysesmentioning
confidence: 99%
“…In order to improve understanding of how hydromorphological variability relates to ecosystem functioning and services, terrestrial biodiversity as well as ground-and surface Huber et al, 2012;Shrestha et al, 2014) and (F) biodiversity surveys (for exact locations see Fournier et al, 2012b). The picture was taken by BHAteam, Frauenfeld.…”
Section: The Record Project At the Thur River (Switzerland)mentioning
confidence: 99%